Does benefit justify research with children? - Binik, A (John Wiley & Sons Ltd, 2017)
The inclusion of children in research gives rise to a difficult ethical question: What justifies children's research participation and exposure to research risks when they cannot provide informed consent? This question arises out of the tension between the moral requirement to obtain a subject's informed consent for research participation, on the one hand, and the limited capacity of most children to provide informed consent, on the other. Most agree that children's participation in clinical research can be justified. But the ethical justification for exposing children to research risks in the absence of consent remains unclear. One prevalent group of arguments aims to justify children's risk exposure by appealing to the concept of benefit. I call these 'benefit arguments'. Prominent versions of this argument defend the idea that broadening our understanding of the notion of benefit to include non-medical benefits (such as the benefit of a moral education) helps to justify children's research participation. I argue that existing benefit arguments are not persuasive and raise problems with the strategy of appealing to broader notions of benefit to justify children's exposure to research risk.